Expansion of educational support : The world Bank and the financing of education ; a thirty-year retrospective - Morgan, John W. [Verfasser]; White, Ian [Verfasser] (My University, 2020)
"The past thirty years have seen a remarkable expansion of the World Bank's programme of educational support. During this period the Bank has established itself as the largest financier of education in the developing world (World Bank 2018). In this article we examinethe trends in World Bank education funding, its research and strategy from 1990s until today. These are placed in the context of successive global advocacy campaigns and of international agreements on education policy targets." (Autorenreferat; BIBB-Doku)
Keywords: World Bank; Bildung; Programm; Schulbildung; Lebenslanges Lernen